15-6x-7x+30=58

Simple and best practice solution for 15-6x-7x+30=58 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15-6x-7x+30=58 equation:


Simplifying
15 + -6x + -7x + 30 = 58

Reorder the terms:
15 + 30 + -6x + -7x = 58

Combine like terms: 15 + 30 = 45
45 + -6x + -7x = 58

Combine like terms: -6x + -7x = -13x
45 + -13x = 58

Solving
45 + -13x = 58

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-45' to each side of the equation.
45 + -45 + -13x = 58 + -45

Combine like terms: 45 + -45 = 0
0 + -13x = 58 + -45
-13x = 58 + -45

Combine like terms: 58 + -45 = 13
-13x = 13

Divide each side by '-13'.
x = -1

Simplifying
x = -1

See similar equations:

| 8(3.14)=r | | 5p+2=-48 | | 0=4(-8+6n)-8(n+8) | | 4x-10-2x-13=2 | | 10(5/2)=w | | 7m^2+4=-16m | | 10-(t-6)=2(4t-1)-7t | | -1+2=3 | | 27-9=52x+40x | | 6s-18=-12+8s | | 4n=7n+9 | | 0.80x-0.30(20+X)=0.95(20) | | 13x-15+3x-40=41 | | 2x-3(x+10)+1=-1+2(x+7)-6 | | 9(x-5)=3(x+3) | | 14+19q=17 | | -0.2x+2=3 | | 14+3n=8n+3(n+4)+2 | | -x+8+3x=6 | | -8n+6b-6b=4b-1-6b | | -33t=99 | | k^2*x^2+2-kx+x^2=0 | | 27-9=-52x+40x | | Xsquare-2x=63 | | -2+6x=-x+82 | | 12=8(k+7)-(-4+2k) | | 8(x+1)-(3x-7)=1 | | -5-8x-12-4x=-89 | | 3(2x+8)=24+6(x-1) | | 9(4y-8)= | | 2(-3+5)+8= | | 6y+1=16y^2 |

Equations solver categories